PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF HAPPY CHEMIST PADA MATERI HIDROLISIS UNTUK MENGUKUR PEMAHAMAN KONSEP SISWA (Jurnal Inovasi Pendidikan Kimia, 2020)
As advances in the world of education, information and communication technology make an extraordinary contribution to the development of science. 2013 curriculum development applies student centered learning patterns, interactive learning patterns, and multimedia-based learning patterns. Chemistry is not enough to simply convey a modification of the learning model, but it is very important to develop a variety of instructional media. The research aims to developing flash-based instructional media are entitled happy chemist to measure student understanding of concepts in hydrolysis material. The research uses research and development types with the method that is modified 4D defining stage (define), design (design), and development (develop). The study was conducted at SMA N 1 Karanganyar, the sampling use purposive sampling technique. The sample are XI IPA 4 and XI IPA 6 class, each of which consists of 36 students. Results of the validation analysis of the feasibility of the media shows the percentage of media validation of 86.69 included in the criteria very well. Questionnaire responses student small scale test and test large-scale gets excellent criteria. The results of the analysis of understanding of concepts based on questions were obtained by 60,56% of students including the category of understanding concepts, 25,98% of students including the category of misconception, 5,90% including the chancy category, while the less understand and not understand categories were 5,38% and 2,17% of all students. Conclusions from the study of media developed proven valid and effective use in learning.